Pipa vs Landa: Game-Based Learning Based on Gamification in Elementary School Mathematics Learning - Matahari Bhakti Nendya; Tiar Dwi Kristianto; Aditya Wikan Mahastama (Universitas Muhammadiyah Sidoarjo, 2025)
Learning is an essential component of human existence. One of the learning opportunities in the educational context is available at school, where instruction is typically delivered orally and accompanied by visuals. Using activities to learn is an option that can increase student interest in certain subjects. Game-based learning is a form of education in which students play a game to aid in their education. This study attempts to employ the Pipa vs. Landa learning game's gift and combo system so that elementary school students are more motivated to learn mathematics. The average GEQ Core Module test results are 4,6 for positive affect, 3,9 for competence, 4,59 for sensory and imaginative immersion, 2,46 for flow, 1,25 for tension, 2,36 for challenge, and 1,39 for negative effect. The average scores on the GEQ Post-Game Module test were 4.36 for positive experience, 1.64 for fatigue, 1.2 for negative experience, and 2.20 for the return to reality. This game provides a superior experience for elementary school students.